Assessing the information quality and usability of My Health Record within a health literacy framework: What's changed since 2016?. Issue 1 (January 2021) - Walsh, Louisa; Hemsley, Bronwyn; Allan, Meredith; Dahm, Maria R; Balandin, Susan; Georgiou, Andrew; Higgins, Isabel; McCarthy, Shaun; Hill, Sophie
Background: This study examined the health literacy demands of My Health Record (MyHR) in the context of preparing for a government-announced opt-out system by repeating two studies of health information and usability conducted in 2016. Objective: To examine whether Australia's MyHR meets the information and usability needs of people at risk of low health literacy and changes since 2016. Method: Content analysis : Informed by the 2016 methods and findings, measures of information quality, themes and target audiences were recorded and reported for each online consumer-facing health information resource. Heuristic evaluation : An evaluation of the MyHR and supporting information website was conducted using a predetermined checklist of usability criteria. A list of usability violations for both websites was identified. Results: Total number of resources grew from 80 in 2016 to 233 in 2018. There was little change since 2016 to average readability levels, target audiences, presentation style, links between resources and usability of MyHR. Compared to 2016, this study demonstrated increases in resources from non-government organisations; video resources; translated resources; and resources with themes of privacy, security and post-registration use. Conclusion: This study identified some improvements in information quality since 2016, but gaps remain in information quality and usability which may negatively impact the ability for people with low health literacy to access and use MyHR. Implications: This study provides a framework for ongoing monitoring and evaluation of the suitability of MyHR for people at risk of low health literacy.